2021
DOI: 10.1016/j.jhsa.2021.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Infection in Thumb Carpometacarpal Surgery After Corticosteroid Injection

Abstract: Purpose The purpose of this study was to determine whether patients who had an intraarticular corticosteroid injection into the thumb carpometacarpal (CMC) joint for the treatment of arthritis within the 3 months before CMC joint arthroplasty or arthrodesis were at increased risk for wound complication/infection and/or repeat surgery for wound complication/infection in comparison with patients who did not receive an injection within 6 months or who received an injection between 3 and 6 months before surgery.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Finally, presurgical steroid injections have been shown to more than double the likelihood of postsurgical revision due to wound complications or infection. 29 Wound complications after CMC arthroplasty are relatively low, reported by Shah et al 13 to be 0.66%. This could account for the overall low rate of reoperation.…”
Section: Discussionmentioning
confidence: 97%
“…Finally, presurgical steroid injections have been shown to more than double the likelihood of postsurgical revision due to wound complications or infection. 29 Wound complications after CMC arthroplasty are relatively low, reported by Shah et al 13 to be 0.66%. This could account for the overall low rate of reoperation.…”
Section: Discussionmentioning
confidence: 97%
“…Different corticosteroids are available, each with specific solubilities to enhance their efficacy in different environments such as tendon sheath or intra-articular. In this review, 7 studies 6,7,13,17,18,21,25 reported the CSI type that surgeons used preoperatively or intraoperatively, most of which were triamcinolone, the least soluble injectable corticosteroid. 4 Insoluble steroid compounds require host hydrolase enzymes to release the active form of the drug; less soluble steroids have a longer half-life.…”
Section: Discussionmentioning
confidence: 99%
“…For example, preoperative CSI given before or within 3 months of the carpometacarpal (CMC) joint surgery showed increased postoperative infection rates in some studies but not in others. 13,14 A review on the temporal effect of perioperative CSI on postsurgical infection rates for procedures of the hand, wrist, elbow, and shoulder has not been published as far as we are aware. There is no consensus on time between preoperative CSI and surgery to reduce subsequent infection rates for many procedures, including shoulder arthroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…As in other orthopaedic subspecialties, the correlation between surgical site infection and recent corticosteroid injection has been examined. The rate of surgical site infection or wound complications for CMC arthroplasty was significantly increased when a corticosteroid injection has been administered to the surgical site within 90 days prior to the surgical procedure 43 . Kirby et al demonstrated a much higher rate of infection after CTR if a corticosteroid injection had been administered preoperatively (mean, 55 days) 44 .…”
Section: Infectionmentioning
confidence: 99%